1991
DOI: 10.1177/001872089103300508
|View full text |Cite
|
Sign up to set email alerts
|

Divided Attention in Experienced Young and Older Drivers: Lane Tracking and Visual Analysis in a Dynamic Driving Simulator

Abstract: A simulated driving task that required the simultaneous execution of two continuous visual tasks was administered to 12 healthy young (mean age 26.1 years) and 12 healthy older (mean age 64.4 years) experienced and currently active drivers. The first task was a compensatory lane-tracking task involving a three-dimensional road display. The second task was a timed, self-paced visual analysis task involving either a vocal or manual binary response to dot patterns projected within the road display. Using adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(75 citation statements)
references
References 11 publications
4
70
0
1
Order By: Relevance
“…However, the type of secondary task used seems to differ with every researcher in the field. Various authors have used visual tasks (Brouwer, Waterink, van Wolffelaar and Rothengatter, 1991, Ephrath and Young, 1981, Verwey and Veltman, 1996, forced-choice tasks This is a preprint of an article submitted for consideration in the Theoretical Issues in Ergonomics Science © 2007 Taylor & Francis Theoretical Issues in Ergonomics Science is available online at: http://journalsonline.tandf.co.uk/ 3 . Miles away.…”
Section: The Debatementioning
confidence: 99%
See 1 more Smart Citation
“…However, the type of secondary task used seems to differ with every researcher in the field. Various authors have used visual tasks (Brouwer, Waterink, van Wolffelaar and Rothengatter, 1991, Ephrath and Young, 1981, Verwey and Veltman, 1996, forced-choice tasks This is a preprint of an article submitted for consideration in the Theoretical Issues in Ergonomics Science © 2007 Taylor & Francis Theoretical Issues in Ergonomics Science is available online at: http://journalsonline.tandf.co.uk/ 3 . Miles away.…”
Section: The Debatementioning
confidence: 99%
“…For instance, Verwey and Veltman (1996) found that while a visual secondary task was a good measure of short-term MWL peaks in driving, it also increased the frequency of steering corrections. Brouwer et al (1991) Theoretical Issues in Ergonomics Science is available online at: http://journalsonline.tandf.co.uk/ 4 . Miles away.…”
Section: The Debatementioning
confidence: 99%
“…Subject (driver) response controls and accessories have included: joysticks (McKnight and McKnight, 1994); steering wheel with response buttons (Brouwer, Waterink, Van Wolffelaar, and Rothengatter, 1991); accelerator and brake pedals (Schiff and Oldak, 1993;Schiff, Arnone, and Cross, 1994); steering wheel with accelerator and brake pedals (Staplin, Lococo, and Sim, 1993;Gianutsos, 1994); self-incorporated unit with seat, instrument panel, steering wheel, and accelerator/brake pedals (Allen, Stein, Aponso, Rosenthal, and Hogue, 1990;Stein, Parseghian, Allen and Haynes, 1990); full vehicle cab with complete instrument panel and.steering wheel, accelerator, and brake pedals (Triggs and Drummond, 1993;Fraser, Hawken, and Warnes, 1994); and a proposed head-mounted-display with steering wheel, accelerator and brake pedals using a virtual environment system currently under development (Levine and Mourant, 1995). These studies examined the effects of visual and cognitive impairments, alcohol and fatigue levels, and other aging characteristics on several driving performance measures.…”
Section: Low-level Simulationmentioning
confidence: 99%
“…Driving simulators are widely used in human factors and transportation research to explore issues in driving behaviour, in part because of this capability. For example, driving simulators have been used to assess driving performance given medical impairments (Findley et al 1989, Rizzo et al 2001, age effects (Brouwer et al 1991, Syzlek et al 1995 and the use of new transportation systems ranging from roadway infrastructure to in-vehicle systems (Stanton et al 2001, Boyle andMannering 2004). All of these applications balance the need for realistic complexity and control.…”
Section: Introductionmentioning
confidence: 99%